Synthesis of extended conjugated indolyl chalcones as potent anti-breast cancer, anti-inflammatory and antioxidant agents - Bhale, Pravin S.; Chavan, Hemant V.; Dongare, Sakharam B.; Shringare, Sadanand N.; Mule, Yoginath B.; Nagane, Samadhan S.; Bandgar, Babasaheb P. (Bioorganic & Medicinal Chemistry Letters, 2017)
In the present investigation, synthesis of a series of extended conjugated delta-chloro-alpha-cyano substituted indolyl chalcones (5a-p) was accomplished by reacting 3-cyanoacetylindole 2 with 3-chloro-3-phenylpropenal 4 in the presence of piperidine. The structural interpretations of newly synthesized compounds were based on chemical and spectroscopic evidences. Anti-tumor evaluation of the synthesized compounds in vitro against MCF-7 (breast carcinoma) cell line revealed that they possess high anti-tumor activities. Among them, compound 5e and 5a demonstrated excellent activity against breast carcinoma (GI(50) <0.1 and mu M respectively) as good as adriamycin (GI(50) <0.1 mu M). The compounds were also screened against the normal Vero monkey cell line, which showed moderate selectivity against inhibition of cancer cells. The effect of extended conjugation on activity authenticated by comparing activity profile of compound 5a, 5i and 5m with their simple analogues. Among the synthesized compounds, 5i and 51 were found to be active anti-inflammatory agents in addition to having noteworthy antioxidant potential. These results suggest the possible use of these compounds for the design and development of novel anti breast cancer agents. (C) 2017 Elsevier Ltd. All rights reserved.

Synthesis and characterization of partially biobased aromatic (Co)polycarbonates containing biphenylene units and pendant pentadecyl chains - Ichake, Amol B.; Nagane, Samadhan S.; Jadhav, Uday A.; Torris, Arun; Grau, Etienne; Cramail, Henri; Wadgaonkar, Prakash P. (Macromolecular Chemistry and Physics, 2022)
2-Pentadecyl-[1,1''-biphenyl]-4,4''-diol (PBD) is synthesized starting from cashew nut shell liquid-a by-product of cashew processing industry. A new series of partially biobased aromatic (co)polycarbonates possessing biphenylene units and pendant pentadecyl chains is synthesized by solution polycondensation of PBD or varying compositions of PBD and bisphenol-A with triphosgene in dry dichloromethane. Inherent viscosities and number average molecular weights of (co)polycarbonates are in the range 0.51-1.24 dL g(-1) and 18 x 10(3)- 43.4 x 10(3) g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. Flexible, transparent, and free-standing films of (co)polycarbonates can be cast from chloroform solution. (Co)polycarbonates are characterized using Fourier transform infrared spectroscopy (FTIR), H-1 NMR, C-13 NMR spectroscopy, X-ray diffraction (XRD), differential scanning calorimetry, and thermogravimetric analysis. T-10 and T-g values of (co)polycarbonates are in the range 417-433 and 8-147 degrees C, respectively. It is demonstrated that the T-g values can be tuned by incorporation of appropriate mol% of PBD as a comonomer in Bisphenol-A-based copolycarbonates. The lowering of the T-g values of (co)polycarbonates can be attributed primarily to the packing disruptive effect of flexible pentadecyl chains. Furthermore, the effect of incorporation of PBD as a comonomer on water contact angle values of (co)polycarbonates is evaluated.
Keywords: aromatic polycarbonates; biobased bisphenol; Cashew nut shell liquid; pentadecyl chain; Renewable resources

Synthesis, characterization and UV-crosslinking of aromatic (Co)polycarbonates bearing pendant azido groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Talanikar, Aniket A.; Lochab, Bimlesh; Wadgaonkar, Prakash P. (ChemistrySelect, 2022)
A new series of (co)polycarbonates bearing pendent azido groups was synthesized by polycondensation of varying molar proportions of 4, 4'-(5-azidopentane-2, 2-diyl) diphenol and bisphenol-A with triphosgene. The chemical structures, compositions and random nature of (co)polycarbonates were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of (co)polycarbonates were in the range 0.63-0.77 dL g(-1) and 35,400-43,400 g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. (Co)polycarbonates could be cast into tough, transparent and flexible films from chloroform solutions. (Co)polycarbonates were further characterized using IR spectroscopy, XRD, TGA and DSC. The thermal crosslinking of (co)polycarbonates bearing pendant azido groups was studied by DSC analysis. Independently, (co)polycarbonates bearing pendant azido groups were exposed to UV irradiation at wavelength of 254 nm and decomposition reaction of azido groups was monitored by FT-IR spectroscopy. The complete decomposition of azido groups was observed with exposure time of 30 min. The formed cross-linked (co)polycarbonates exhibited improved % char yield values compared to parent (co)polycarbonates. The measurement of mechanical properties of representative crosslinked (co)polycarbonates indicated increase in tensile strength and Young's modulus and decrease in % elongation compared to corresponding parent linear (co)polycarbonates.
Keywords: Aromatic polycarbonate; Pendant azido group; solution polycondensation; Triphosgene; UV-crosslinking

Synthesis, characterization and post-modification of aromatic (Co)polyesters possessing pendant maleimide groups - Jadhav, Uday A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P. (High Performance Polymers, 2023)
A new series of (co)polyesters possessing pendent maleimide groups was synthesized by low temperature solution polycondensation of 4, 4’-(5-maleimidopentane-2, 2-diyl) diphenol (BPA-MA) with isophthalic acid chloride (IPC), terephthalic acid chloride (TPC) and a mixture of TPC and IPC (50:50 mol %). Copolyesters were also synthesized by polycondensation of varying compositions of BPA-MA and bisphenol-A (BPA) with IPC. The chemical structures and compositions of (co)polyesters were confirmed by NMR spectroscopy. Inherent viscosity values and number-average molecular weights of (co)polyesters were in the range 0.50–0.76 dL/g and 17,700-32,100 g/mol, respectively, indicating the formation of reasonably high molecular weight polymers. (Co)polyesters were readily soluble in common organic solvents and could be cast into tough, transparent and flexible films from chloroform solutions. (Co)polyesters exhibited 10% weight loss and glass transition temperatures in the range 464–468 and 142–178°C, respectively. A representative copolyester possessing pendant maleimide groups was chemically modified via metal-free azide-maleimide 1,3-dipolar cycloaddition click reaction with two azido compounds, namely, (azidomethyl)benzene (Bz-N3) and 1-(azidomethyl)-pyrene (Py-N3) to yield corresponding modified copolyesters in a quantitative manner.